Anchusa italica Retz. Hydro-Alcoholic Extract through Attenuation of Oxidative Stress Exerts an Anticonvulsant Effect on the Pentylenetetrazole-Induced Seizure in Mice - Rahimi-Madiseh, Mohammad; Nasiri-Boroujeni, Shakiba; Lorigooini, Zahra; Nazari, Meysam; Sadeghian, Reihaneh; Rafieian-Kopaei, Mahmoud; Amini-Khoei, Hossein (International Journal of Epilepsy, 2021)
Introduction It has been shown that oxidative stress is involved in the pathophysiology of seizure. Current anticonvulsants have side effects, thus further studies are needed to find new agents with low side effects. Anchusa italica Retz. has been suggested to have antioxidant and neuroprotective effects. The present study aimed to determine the anticonvulsant effects of A. italica hydro-alcoholic extract on pentylenetetrazole (PTZ)-induced seizures in mice focusing on its possible antioxidative stress properties.Materials and Methods Sixty mice were randomly divided into six groups. The intervention groups received the A. italica extract at the doses of 50, 100, and 200 mg/kg, 30 minutes before the injection of PTZ, whereas the positive control group received phenobarbital. The seizure threshold was then recorded.Results A. italica extract significantly increased the seizure threshold. The extract significantly increased serum and prefrontal cortex total antioxidant capacity compared with the control group. The A. italica extract significantly reduced serum and prefrontal cortex malondialdehyde and nitrite levels compared with the control group.Conclusions The results showed the anticonvulsant effects of A.italica extracts on the PTZ-induced seizure in mice is partially due to the attenuation of oxidative stress.
Keywords: seizure; Anchusa italica Retz. extract; oxidative stress; mice